Peran Kepala Sekolah Dalam Melakukan Kontrol Mutu Pendidikan - Noer Rohmah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2018)
Controlling is a part of the management function. This function held to evaluate and enhance teacher performance or other personnel who involved in the education process. the aim of controlling is to ensure the best accomplishment has been planned. There are several strategy needed by principals to enhance education quality: (1) enhance teacher professionalism and welfare; (2) upgrade the material; (3) upgrade the method; (4) upgrade equipment; and (5) upgrade learning motivation. Besides that, there are several strategi need to enhance competitiveness: (1) defensive strategy; (2) survival strategy (3) adaptive strategy; (4) competitive oriented strategy.